AKIBAT HUKUM TERHADAP PELAKU PELANGGAR HAK CIPTA KARYA CIPTA LAGU DIKAJI BERDASARKAN UNDANG-UNDANG HAK CIPTA NOMOR 28 TAHUN 2014 DAN COPYRIGHT ACT (CHAPTER 63, REVISED EDITION 2006) - Raden Ayu Putu Wahyu Ningrat; Dewa Gede Sudika Mangku; I Nengah Suastika (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2020)
The purpose this research were to find out abutment doing download of song through sites on the internet and to find out and analyze of the legal consequences related to the offender copyright song work downloaded through a sites at internet. The type of reasearch used is a type of normative legal research. The approach that used in this research was statue approach and comparative approach. The research obtained the data from the result of analysis Act number 28 of 2014 (UUHC) and Copyright Act (Chapter 63, Revised Edition 2006) (Singapore). The results of the research are (1) not all song downloaded through a sites at internet it means infringement of copyright (2) the legal consequences for offenders of copyright downloading songs through a site on the internet based on the civil law the creator can claim compensation, but clarity is still needed regarding the amount of compensation, while based on the criminal law, the criminals of the perceived parties disadvantage could be subject to sanctions in the form of imprisonment or fine.